Social, Economic, and Technological Barriers of the Music Industry in Cebu Province Through the Lens of Management Functions - Almaden, Antoniette M.; Ocampo, Alex P.; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research aimed to investigate the multifaceted challenges faced by music core groups in Cebu Province, analyzing social, economic, and technological barriers. Its primary goal was to propose an innovative management framework for ensuring sustainable growth in the music industry. Utilizing qualitative multiple-case study, this study delved into the complex landscape shaped by challenges for music creators, artists, and organizations. It involved a comprehensive management framework encompassing planning, organizing, leading, and controlling. The study identified themes including navigating professional dynamics, social equity and empowerment dynamics, obstacles in creative pursuits, financial sustainability, economic instability, challenges in technology utilization, and industry adaptation. Various coping mechanisms such as faith, self-care, and community involvement were observed. While the study provided valuable insights, the limited representation of diverse industry positions highlights the need for further research to fully grasp the complexities and challenges of the music industry. The Amplify Cebu Music Management Framework, incorporating TechHarmony Integration, aimed to seamlessly integrate technology into the industry. Tailored interventions addressed leadership development, promotion strategies, artist well-being, creative hubs, education, and government support. The study's insights transcend the local context, offering globally applicable frameworks for fostering inclusive and effective industry development, thereby enhancing social equity and empowerment dynamics. This research presents a comprehensive roadmap for overcoming barriers and enhancing resilience, contributing to a vibrant and sustainable music industry in Cebu while aligning local scenes with global audiences.